2001
DOI: 10.1097/00001756-200109170-00023
|View full text |Cite
|
Sign up to set email alerts
|

BDNF and NT3 extend the critical period for developmental climbing fibre plasticity

Abstract: The effect on neonatal brain plasticity of two neurotrophins, brain derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3), was studied using the rat olivocerebellar projection as a model. Unilateral transection of climbing fibres (CFs) in the rat before postnatal day 7 induces reinnervation of the deafferented hemicerebellum, but this does not occur if the transection is performed after postnatal day 10. Eleven-day-old day rats underwent unilateral CF transection followed by neurotrophin injection into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 24 publications
0
33
0
Order By: Relevance
“…When either BDNF or NT-3 was applied to the whisker pads following neonatal denervation, barrel patterns developed in a manner more consistent with normal development (Calia et al, 1998). In another study, reinnervation of cerebellum occurred if climbing fibers were transected prior to postnatal day 7 in the rat, but reinnervation occurred only after the addition of exogenous BDNF or NT-3 if transection was given at later ages (Sherrard and Bower, 2001). Such studies not only lend further support for the role of neurotrophic regulation following denervation during developmental sensitive periods, but also provide impetus to determine if exogenous application of neurotrophins following neonatal CTX might result in maintenance of papillae and taste buds.…”
Section: Discussionmentioning
confidence: 92%
“…When either BDNF or NT-3 was applied to the whisker pads following neonatal denervation, barrel patterns developed in a manner more consistent with normal development (Calia et al, 1998). In another study, reinnervation of cerebellum occurred if climbing fibers were transected prior to postnatal day 7 in the rat, but reinnervation occurred only after the addition of exogenous BDNF or NT-3 if transection was given at later ages (Sherrard and Bower, 2001). Such studies not only lend further support for the role of neurotrophic regulation following denervation during developmental sensitive periods, but also provide impetus to determine if exogenous application of neurotrophins following neonatal CTX might result in maintenance of papillae and taste buds.…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, data obtained in experimental animals indicate that NTs may have a role in repair of cerebellar neurons and connectivity. In fact, it has been reported that the BDNF and NT-4 rescue cerebellar granule neurons from oxidative stress-mediated apopotic death (Skaper et al, 1998) and several lines of evidence brought to attention the trophic role of NTs on cerebellar afferent neurons (Shibayama et al, 1998;Rabacchi et al, 1999;Sherrard and Bower, 2001). Positive structures for each NT were observed in all specimens examined.…”
Section: Nts Tissue Localizationmentioning
confidence: 82%
“…We also investigated the effects of LI-rMS on the expression of four candidate genes, which are involved in olivo-cerebellar development and plasticity (Morrison and Mason, 1998; Sherrard and Bower, 2001; Avella et al, 2006; Bosman et al, 2006; Zhang et al, 2007; Sherrard et al, 2009; Sherrard et al, 2013). Although, it has been shown that magnetic stimulation alters gene expression in different neuronal populations in vivo and in vitro (high intensity: Funke and Benali, 2011; Stock et al, 2012; Vlachos et al, 2012; Ma et al, 2013, low intensity: Rodger et al, 2012; Makowiecki et al, 2014; Grehl et al, 2015) we show for the first time stimulation-related effects of LI-rMS on cerebellar and inferior olive tissue.…”
Section: Discussionmentioning
confidence: 99%